Fundamental investigation on effect of microencapsulated water on expansion behavior of microcapsules. (3rd April 2019) - Taguchi, Yoshinari; Saito, Natsukaze; Fuchigami, Kiyomi; Tanaka, Masato
Abstract : The microcapsules containing water were prepared with the suspension polymerization method, and the fundamental investigation was performed to make the effect of microencapsulated water on expansion behavior of microcapsules clear. In the experiment, only the volume of water added into styrene monomer was changed to make the effect of microencapsulated water volume clear, and three kinds of water contents were measured: namely, the initial water content for the microcapsules just after preparation, the middle water content for the microcapsules dried at 44°C for 24 hours, and the final water content for the microcapsules dried at 110°C for 1 hours. With increasing the added water volume, the initial water content increased; the middle water content decreased after increasing halfway through, and the final water content gradually decreased. Also, with increasing the added water volume, the drying rate of the microcapsules increased and the expansion ratio decreased. The water volume required to expand the microcapsules, in other words, the critical shell thickness required to prevent evaporation of water and to contribute to expansion of microcapsules is discussed.